IN VITRO ANTI-INFLAMMATORY ACTIVITY OF BLUE-GREEN ALGAE-GEITLERINEMA SPLENDIDUM COLLECTED FROM WESTERN GHATS, SOUTH INDIA - J, Krishnaveni; Mangai S, Alarmal; Jency I, Mary (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Geitlerinema splendidum is non-edible blue-green algae available in freshwater systems. It belongs to the family Pseudanabaenacae genera. In exploring the medical properties of algae, our present work aimed to analyze the anti-inflammatory effect of the algae G. Splendidum. Methods: Anti-inflammatory activity was done by human red blood cell membrane stabilization assay for ethyl acetate and ethanol crude extracts of alga and found that the ethyl acetate extract has better inhibitory property than ethanol crude extract. Diclofenac was used as the standard drug. Results: The experimental results obtained are comparable to the reference drug and are found to be dose-dependent. Even at a minimum concentration of 12.5 μg/ml, the percentage inhibition was in the range of 56.6±0.12–58.5±0.03 %, which indicated that the alga G. splendidum has a satisfactory anti-inflammatory activity. Conclusion: Our present work is supposed to be the first report in exploring the anti-inflammatory effect of the algae G. splendidum.